The Theme of Death and Eternity in Emily Dickenson’s Poetry - Petrosyan, Gayane (Armenian Folia Anglistika, 2008)
The poetry of the world-renowned poetess Emily Dickenson received general acclaim in the fifties of the previous century, 70 years after her death. This country-dwelling lady who had locked herself from the surrounding world, created one of the most precious examples of the 19th century American poetry and became one of the most celebrated poets of all time without leaving her own garden.Her soul was her universe and the mission of Dickenson’s sole was to open the universe to let the people see it. Interestingly, most of her poems lack a title, are short and symbolic. The poetess managed to disclose the dark side of the human brain which symbolizes death and eternity.